(untitled) (Transport systems and technologies, 2024)
For the implementation of a mixed type of transportation on the territory of Ukraine, a stable saddle for transporting cargo semi-trailers without a tractor on railway platforms of the 13-9004M model was developed and manufactured. This device for the transportation of cargo semi-trailers is a four-sided structure of the "Eiffel Tower" type, the lower plane of which is fixed on the platform car through the plate with the help of bolted connections. This work describes the running tests of the 13-9004M model platform car with a saddle rack installed on it for the transportation of cargo semi-trailers without a tractor. According to the results of the tests of the saddle rack for the transportation of semi-trailers on the platform wagon model 13-9004M, the maximum values of the stresses that occur in the structure of the saddle rack during running strength tests, as well as compliance with such indicators as the coefficient of vertical dynamics of the sprung mass of the cart, the coefficient of vertical dynamics of the unsprung mass, were determined trolley frame, coefficient of horizontal dynamics, coefficient of reserve of stability of the wheel from derailment.